Práticas corporais e atividades físicas no cuidado com a obesidade: análise de planos de ação de profissionais da saúde do estado de Goiás fundamentada na saúde coletiva - Sousa, Priscylla de Moraes (2022)
Obesity remains, over the years, as a major public health problem, employing the research guidelines in the health field. Among its meanings, the etiology of obesity is linked to biopsychosocial issues, allowing various ways of interpreting the phenomenon. In the last years, one can notice the rise of critical and problematizing strands on the subject, which emphasize the need for integrality of its characterization (interrelation of biological sciences such as social and human sciences) and show that, in addition to a health problem, obesity is a result of social production. Being a relevant theme to the field of Physical Education, obesity, bodily practices (CP) and physical activity (PA) are the main themes of this dissertation. In order to contribute to the growing debates about the dialectical process of health-illness-care, we based our research on the ideological understandings of the theoretical and practical field of Collective Health, which integrates with the approaches and knowledge of critical/social epidemiology. We challenged ourselves to apply this conceptual framework to the actions of attention and care for the obese person in the Unified Health System (SUS) through action plans, a product of the conclusion of the continuing education course: "Actions to confront and control obesity within the SUS in the state of Goiás" for health professionals. Thus, our objective was to analyze the perspective of the training course for health professionals in SUS and the proposals of action plans that articulate the themes CP and PA in obesity care in municipalities of the state of Goiás, in the light of the conceptual basis of critical/social epidemiology. As a methodological procedure we used the techniques of document analysis and thematic analysis, investigating respectively the course content and the action plans developed by the trainees. In step with demarcating the conceptualizations and understandings (of the course and of the course participants) about obesity, CP, and PA, we established categorizations based on the notion of Social Determination of Health, in its general, particular, and individual dimensions. We found that most of the plans still reflect the hegemonic biomedical thinking, indicating approaches focused on biophysiological and behavioral aspects. However, we can also infer signs of health promotion focused on a progressive and social perspective. Thinking these themes from broader and sociocritical references allows the advancement in positioning and directions of the field through a critical language of reality and collaborating to the construction and reorientation of actions in the health-disease-care processes.